Development and Evaluation of Ontologies in Traditional Medicine: A Review Study - Shojaee-Mend, Hassan; Ayatollahi, Haleh; Abdolahadi, Azam (Methods of Information in Medicine, 2019)
Background Development of ontologies in traditional medicine can be a foundation for other applications of informatics in this field. Despite the importance of the development of ontologies in traditional medicine, there are few review studies in this area. This study aims to review different methods for ontology development and evaluation in traditional medicine.Methods This review study was performed in 2019. To find related papers, six databases including Scopus, Web of Science, PubMed, Embase, IEEE Xplore, and SpringerLink were searched. Initially, 761 articles were identified. After applying inclusion and exclusion criteria, 22 articles were selected to review different methods for ontology development and evaluation in traditional medicine.Results Five different methods were used for ontology development in traditional medicine, namely conventional, customized, semiautomatic, upper-level, and large-scale methods. The results showed that ontology evaluation was only considered in 32% of the studies. The common methods used for ontology evaluation were competency questions, expert-based evaluation, and automatic detection of inconsistency errors.Conclusion Development of ontologies is of high importance for organizing knowledge in traditional medicine, as this branch of medicine is often not documented or is documented in local languages. The results of this study can help ontology developers to be familiar with the common methods of ontology development and evaluation in traditional medicine and use them for future research.
Keywords: traditional medicine; ontology development; ontology evaluation